Severe dilated cardiomyopathy undergoing emergency lower segment cesarean section: A case report - Sunil Thakur (Journal of Obstetric Anaesthesia and Critical Care, 2020)
Dilated cardiomyopathy (DCM) is a rare condition in pregnancy and has an established grave prognosis as such. Anesthetic management of pregnant patients with dilated cardiomyopathy is quite challenging either because of preexisting DCM or the risk of precipitating sudden cardiac failure. Pregnancy in patients with preexisting DCM can further flare-up disease and can be life- threatening, especially in patients who land up in an emergency when there is less time to optimize the patient's condition. The anesthesiologist thus must have knowledge of its causes, pathophysiology, clinical features, and various anesthetic modalities available. The present case report illustrates the successful management of a parturient with preexisting DCM undergoing emergency caesarean section. It is very important that patients with DCM should have regular follow-up so that timely intervention can be done about the mode of delivery for the safety of both mother and child.